Jan Kochanowski’s “Nagrobek kotowi” in the perspective of ecocriticism - Knopik, Agata (Melusine. Old Literature and Culture, 2023)
The article attempts to use the optics of human-animal studies shaped by this contemporary methodology. It tries to verify the existing interpretations of the animal epitaph as manifestation of humour. In order to resign from anthropocentric look at the poem it is written without the intention of amusing the reader. The article transforms ancient, medieval and biblical inspirations. The tombstone was interpreted with a contextual reference to the epic poem “O kocie” to unravel the meaning of the phrase “to pull the cat” (or to pull smb. legs). The use of the ecocritical perspective made it possible to show that despite the pre-modern visions of nature prevailing in culture with a hierarchical order of the chain of beings. Kochanowski found in the conventions space to express the community of experiencing the fate of biological mortality, empathy, the sensitivity of conscience and responsibility for lesser brothers.